PENGARUH MODEL GUIDED INQUIRY LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK SD NEGERI 1 BINA KARYA UTAMA - Nur'Afifah, Silmi; Muhisom; Abung, Miranda; Destini, Frida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this research was the low understanding of mathematical concepts of fourth grade students of SD Negeri 1 Bina Karya Utama. This research aimed to determine the effect of the guided inquiry learning model on students understanding of mathematical concepts. This research method is quantitative. This study used a non-equivalent control group design. This population in this study consisted of 86 students. The study used non-propability sampling technique type purposive sampling. The sample used was 56 students, consisting of 27 students in the experimental class and 29 students in the control class. Data collection techniques using test tecniques in the form of description questions and non-test techniques in the form of observasion sheets. Hypothesis testing using simple linear regression test. Testing this hypothesis, there was an effect of applying the guided inquiry learning model on the understanding of mathematical concepts of SD Negeri 1 Bina Karya Utama students by 62,5%.